AUTOMATIC CONSISTENCY VERIFICATION OF MECHANICAL CAD FILES - PERNG, DB; CHEN, Z; WU, JS (My University, 1993)
A system for automatic verification of the exactness of the CAD files of a mechanical part with planar and cylindrical faces through 3D part reconstruction is described. A set of consistency checking rules are specified to facilitate the part reconstruction. The system not only reconstructs the 3D geometry from a correct drawing file, but also produces adequate error messages to aid the designer to make corrections. We shall present our method with illustrations. Experimental results indicate that the set of checking rules is very useful and the system is very effective.